Alleviating Loneliness and Promoting Social Distancing: The Role of Mitsu Desu Game in Japan’s COVID-19 Response - Löschke, Ayaka (19. Deutschsprachiger Japanologentag, 2025)
This presentation examines how digital entertainment, specifically social distancing video games, played a significant role in alleviating loneliness and promoting social distancing during Japan’s COVID-19 pandemic. A prominent example is Mitsu Desu Game, developed by amateur creators, where players take on the role of a super-powered Tokyo governor tasked with detecting and dispersing crowds to enforce social distancing measures. By analyzing data from platforms such as UnityRoom, Twitter, and YouTube, this presentation identifies three crucial factors contributing to the game’s impact in 2020: (1) its ability to influence players’ spatial awareness, reinforcing adherence to social distancing practices, (2) the role of online platforms in fostering the creation of online communities that helped mitigate feelings of isolation and loneliness, and (3) the integration of political figures into pop culture narratives, which significantly enhanced the game’s visibility and appeal. Additionally, this presentation will discuss the broader implications of how such digital entertainment can serve not only as a form of engagement but also as an innovative tool for public health communication and community building during times of crisis. This analysis underscores the potential of digital media to address pressing social issues and supports public health strategies in unique and effective way
Keywords: Mitsu Desu Game; video game; COVID-19; social distancing; loneliness; Japan